2021
DOI: 10.1021/acs.energyfuels.1c00628
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Xylose to Furfural Catalyzed by Carbon-Based Solid Acid Prepared from Pectin

Abstract: Furfural is an important platform chemical that can be produced by dehydration of pentose, which is an important building block of lignocellulosic biomass. In this study, xylose was chosen as the reaction substrate, and a carbon-based solid acid prepared from pectin was used as the catalyst in a mixed solvent consisting of water and γ-valerolactone (GVL). FTIR results showed that the sulfonated catalyst had typical characteristic peaks of sulfonic groups, while the results based on NH3-TPD and elemental analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In particular, heterogeneous solid‐acid catalysis is preferred because of the option of easy separation and reuse of the catalyst [24] . This practice could significantly reduce the overall processing cost of a product during large‐scale manufacture [25] . Moreover, the bio‐based fuel range chemicals have the potential to reduce dependency on fossil reserves and the impact on the environment (greenhouse gas emissions) [26] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, heterogeneous solid‐acid catalysis is preferred because of the option of easy separation and reuse of the catalyst [24] . This practice could significantly reduce the overall processing cost of a product during large‐scale manufacture [25] . Moreover, the bio‐based fuel range chemicals have the potential to reduce dependency on fossil reserves and the impact on the environment (greenhouse gas emissions) [26] .…”
Section: Introductionmentioning
confidence: 99%
“…[24] This practice could significantly reduce the overall processing cost of a product during large-scale manufacture. [25] Moreover, the bio-based fuel range chemicals have the potential to reduce dependency on fossil reserves and the impact on the environment (greenhouse gas emissions). [26] Typical acidic catalysis of glucose ends with the levulinic acid (LA) formation by engaging the sequential isomerization and dehydration mechanisms to yield fructose and HMF intermediates, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Processes 2021, 9, 2269 2 of 10 pectin [30], etc., have been discovered and utilized for furfural production. Very recently, biomass-based heterogeneous catalysts, including carbon, sucrose [31], miscanthus [32], and lignin [33], have gained considerable interest due to the utilization of available, inexpensive, and renewable biomass as a carrier.…”
Section: Introductionmentioning
confidence: 99%
“…In five cycles, no significant decrease in activity was observed after the initial deactivation. Xu et al 27 pyrolyzed pectin from orange peel and then sulfonated it with concentrated sulfuric acid. It was found that the acid concentration and acid distribution on the surface of the catalyst could be controlled by the sulfonation temperature.…”
Section: Development and Classification Of Carbon-based Solid Acidsmentioning
confidence: 99%